Pengelolaan Zakat di Era Disrupsi: Studi Meta Analisis - Ade Nur Rohim; Prima Dwi Priyatno; Lili Puspita Sari (Islamic Economics and Business Faculty of UIN Antasari, 2021)
The development of technology in the digital era is an absolute thing. Various activities and community activities are required to adapt to the use of technology and various digital-based media. Zakat management is one of the various activities in the community that are also encouraged to adapt. This study aims to map research on digital zakat management. A qualitative research approach was used in this study with meta-analytical methods and descriptive statistics processed from a literature review of 52 articles related to the digitization of zakat management. The results of this study indicate that the number of digital zakat management publications continues to increase. Several aspects were studied related to the digital zakat development and accountability strategy. This study recommends the basis for selecting relevant strategies in zakat management in the digital era by referring to various studies that have been carried out. Perkembangan teknologi di era digital menjadi suatu hal yang mutlak terjadi. Berbagai aktivitas dan kegiatan masyarakat dituntut untuk beradaptasi dalam pemanfaatan teknologi dan berbagai media berbasis digital. Pengelolaan zakat menjadi salah satu dari berbagai aktivitas di masyarakat yang turut didorong untuk beradaptasi. Penelitian ini bertujuan untuk memetakan penelitian mengenai pengelolaan zakat digital. Pendekatan penelitian kualitatif digunakan pada penelitian ini dengan metode meta analisis dan statistik deskriptif yang diolah dari kajian pustaka terhadap 52 artikel terkait digitalisasi pengelolaan zakat. Hasil penelitian ini menunjukkan bahwa peningkatan jumlah publikasi pengelolaan zakat digital terus meningkat. Beberapa aspek yang dikaji terkait strategi pengembangan dan akuntabilitas zakat digital. Penelitian ini merekomendasikan dasar pemilihan strategi yang relevan dalam pengelolaan zakat di era digital dengan mengacu pada berbagai penelitian yang telah dilakukan.